PENDEKATAN MODEL PEMBELAJARAN MONTESSORI PADA PENDIDIKAN ANAK USIA DINI - Ngewa, Herviana Muarifah; Hasis, Pertiwi Kamariah (Institut Agama Islam Negeri Bone, 2022)
This article aims to explain the concept of a Montessori learning approach in early childhood education in schools. The Montessori approach pays attention to the development of the sensitive period of the child through various things such as the nature of the child, freedom, growth and development, as well the role of the environment and off spring. For children who have to carry out the Montessori curriculum program so that there is a suitability and relationship between the behavior caused by children at school and at home. There teacher must apply the process of childrens activities in accordance with the concepts in Montessori learning such as approaches, methods, learning resources, and steps. Montessori learning so that children feel free to participate in the learning process.